Harvesting vibration energy using piezoelectric material: modelling, simulation and experimental verifications - Fakhzan , M. N.; Abdul Muthalif, Asan Gani (Elsevier, 2012)
Piezoelectric materials produce charges when subjected to dynamic strain. These materials can be used to capture and store vibration energy and then used to power up small devices. This paper presents analytical estimation of voltage production of piezoelectric cantilever beam when subjected to base excitation with and without attaching proof masses. The beam is modeled using Euler Bernoulli which is also known as thin beam theory. As such, the model obtained here is applicable for micro and nano-beams. The frequency response function (FRF) that relate the output voltage and transverse acceleration are identified for multi-mode vibration. These analytical predictions are then compared with the experimental results and good agreement is obtained.